Profitability Of Onion Cultivation In Some Selected Areas Of Bangladesh (Bangladesh Journal of Agricultural Research, 2011)
The present study was conducted in three major onion growing districts to estimate the profitability of onion cultivation. Total of 150 onion farmers taking 50 farmers from each area were selected randomly. The cost of onion cultivation was found to be Tk 93517 per hectare on total cost basis. Seedling cost (41%) was the major cost item followed by human labour cost (24%). The yield of onion was found 9869 metric tons per hectare. The gross margin and net return were found to be Tk. 85308 and 79487 per hectare, respectively. The benefit cost ratio was found 1.85. Inputs like human labour, seedling, manures, urea, TSP, irrigation, and insecticide had positive effect on the yield of onion. The profit obtained from onion cultivation was found higher than that of other competitive crops like mustard, groundnut, and cabbage. Non-availability of HYV onion seed at proper time, lack of technical knowledge, high price and non-availability of fertilizer in time, lack of appropriate storage facility were the major problems of onion cultivation in the study areas and needs immediate attention to solve these problems. Keywords: Onion; input use pattern; profitability DOI: http://dx.doi.org/10.3329/bjar.v36i3.9271 BJAR 2011; 36(3): 427-435